2009
DOI: 10.1007/s12374-009-9083-1
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of High Levels of ABA Regulates the Pleiotropic Response of the nhr1 Arabidopsis Mutant

Abstract: Plants have evolved a variety of mechanisms for responding to environmental cues, which allows them to survive in the presence of limited resources or environmental stresses. One of the most significant growth adaptations plants have attained is tropism, a growth response that involves bending of plant organs toward or away from a stimulus. Roots exhibit hydrotropism in response to moisture gradients, which is thought to be critical in acquiring water and establishing their stand in the soil. However, the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
2
11
0
3
Order By: Relevance
“…Even though this suggested that the abamineSG treatment could mimic an ABA defi cient phenotype on hydrotropism, it also implies that hydrotropism is not solely controlled by ABA because the hydrotropic curvature was not completely suppressed. Previously, abamineSG was shown to restore the hydrotropic response to about 70% of treated nhr1 seedling roots ( Quiroz-Figueroa et al, 2010 ). To a large extent, these results reveal that environmental cues, such as light and water stress, mediated by ABA and cytokinin signaling control the activity of the genes that participate in hydrotropism ( Fig.…”
Section: Historysupporting
confidence: 59%
See 1 more Smart Citation
“…Even though this suggested that the abamineSG treatment could mimic an ABA defi cient phenotype on hydrotropism, it also implies that hydrotropism is not solely controlled by ABA because the hydrotropic curvature was not completely suppressed. Previously, abamineSG was shown to restore the hydrotropic response to about 70% of treated nhr1 seedling roots ( Quiroz-Figueroa et al, 2010 ). To a large extent, these results reveal that environmental cues, such as light and water stress, mediated by ABA and cytokinin signaling control the activity of the genes that participate in hydrotropism ( Fig.…”
Section: Historysupporting
confidence: 59%
“…Because hydrotropism might be one of the plant mechanisms for avoiding water stress and ABA is traditionally considered as the water stress hormone ( Finkelstein, 2006 ), it was not surprising that the no-hydrotropic phenotype of the nhr1 mutant ( Fig. 1B ) was signifi cantly intensifi ed with ABA or inhibited with abamineSG, a specifi c inhibitor of ABA biosynthesis ( Kitahata et al, 2006 ;Quiroz-Figueroa et al, 2010 ). Additionally, ABA treatment inhibited hydrotropism of wild-type is lost as bending root tips attained an angle of 40 ° to the horizontal, a mechanism that seems to reverse this asymmetric fl ow at the midpoint of root bending ( Band et al, 2012 ).…”
Section: Historymentioning
confidence: 99%
“…4), we next investigated the effects of ABA on postgermination growth. Inhibition of seedling root growth is a typical action of ABA (Quiroz-Figueroa et al, 2010;Ryu et al, 2010). As shown in Figure 5A, atairp2 and 35S:AtAIRP2-sGFP plants displayed hyposensitivity and hypersensitivity, respectively, to ABA in terms of young root growth.…”
Section: Atairp2 Is Positively Involved In Aba-mediated Root Growth Imentioning
confidence: 95%
“…Although the genes responsible for these mutants have not yet been identified, physiological studies of the semidominant mutant, nhr1, showed abnormal root tip cells and enhanced gravitropism (Eapen et al, 2003). Subsequent reports have suggested that nhr1 exhibits pleiotropic phenotypes, most of which can be explained by enhanced accumulation of the phytohormone ABA (Ponce et al, 2008;Quiroz-Figueroa et al, 2010). In addition, these authors showed that ABA treatment of wild-type roots not only reduces the starch granules in the root tip but also produces enhanced gravitropism.…”
Section: Molecular Identification Of Genes Responsible Formentioning
confidence: 99%
“…Subsequent reports have suggested that nhr1 exhibits pleiotropic phenotypes, most of which can be explained by enhanced accumulation of the phytohormone ABA (Ponce et al, 2008;Quiroz-Figueroa et al, 2010). Although these findings have led to the hypothesis that ABA negatively regulates root hydrotropism (Ponce et al, 2008;Quiroz-Figueroa et al, 2010), the roots of some ABA-deficient andinsensitive mutants have shown reductions in both hydrotropism and gravitropism . Although these findings have led to the hypothesis that ABA negatively regulates root hydrotropism (Ponce et al, 2008;Quiroz-Figueroa et al, 2010), the roots of some ABA-deficient andinsensitive mutants have shown reductions in both hydrotropism and gravitropism .…”
Section: Molecular Identification Of Genes Responsible Formentioning
confidence: 99%